Model Analysis (SWOT) Of Curriculum Development From Civic Education At 21 Century, 4.0 Era In Indonesian - Gunawan Santoso (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Civic Education curriculum from year 1975-2013 are ultimately aims to make citizens say, act, and behave, based on Pancasila or spirit in everyday life that are run from the time school education to become a high school mature and become the pride of the nation bless yourself, family, school, state and nation with the moral soul/good and intelligent character who can advance and competitive in national and international era. Design/methodology/approach: Civic Education solution 21 century 4.0 Indonesian is through a process at body of knowledge of learning and practice of students in the school are monitored and assessed as a form of moral evaluation and student behavior. Opportunities Civic Education still need a lot of development in the scientific body of knowledge. Findings: Civic Education strength is on the Pancasila, the 1945 Constitution, values, morals, local knowledge and diversity in cultured. There are weaknesses in the teaching of Civic Education monotonous and more innovative not only focuses on the cognitive, affective and psychomotor while dispensed and not included on the national exam. Research limitations/implications: Threats Civic Education and free sex number of students who make the nation weak morals and act not see the value of Pancasila (say and behave without values). Practical implications: State your implication here Originality/value: This paper is original Paper type: Research paper.